Determinants of Doppler confirmed lower limb atherosclerosis in asymptomatic type 2 diabetes: cross-sectional evidence from a tertiary centre in South India - Krishnaswamy, Priyadharshini; M. L., Ashok; Krishnegowda, Chetana (International Journal of Research in Medical Sciences, 2025)
Background: Peripheral artery disease (PAD) in type 2 diabetes is frequently asymptomatic yet clinically significant, has multifactorial risk factors, the identification of which enable appropriate preventive strategies. Aims of study were-to identify clinical and biochemical determinants of Doppler‑confirmed lower‑limb atherosclerosis (PAD) in asymptomatic adults with type 2 diabetes and to establish the in- hospital prevalence of PAD in the study population. It was an observational cross‑sectional study conducted at a tertiary care centre in South India. Methods: Adults ≥40 years with type 2 diabetes, asymptomatic for PAD were screened for PAD using colour duplex doppler, those with PAD were evaluated for demographic factors, diabetes duration, glycaemia (HbA1c), lipid profile, and diabetes complications [retinopathy, proteinuria/renal involvement, neuropathy, and coronary artery disease (CAD)]. Statistical analysis used was χ²/Fisher’s exact test for categorical variables and Welch’s t‑test for continuous variables. Analyses were performed in R, version 4.1.1 Results: Among 320 participants, PAD prevalence was 41.9% (n=134). PAD was associated with older age, longer diabetes duration, higher HbA1c, lower HDL and higher triglycerides, as well as retinopathy, proteinuria/renal involvement, neuropathy, and coronary artery disease (all p<0.001). Gender, LDL cholesterol and total cholesterol were not associated significantly with PAD (p>0.05). Conclusions: Age, glycaemic burden, atherogenic dyslipidaemia, and microvascular/atherosclerotic comorbidities can help identify higher‑risk subgroups for targeted PAD screening in asymptomatic type 2 diabetes.